Cosmic-quantum connections: Assessing the viability of weak gravity and weak cosmic censorship conjectures in Kerr-Newman-Kiselev-Letelier black hole - Saeed Noori Gashti; Behnam Pourhassan (Physics Letters B, 2025)
This paper addresses a potential validation of the weak gravity conjecture (WGC) with the weak cosmic censorship conjecture (WCCC), as a significant challenge in quantum gravity. We explore the viability of the WGC and WCCC in the context of the Kerr-Newman-Kiselev-Letelier (KNKL) black hole. Although these conjectures appear unrelated, but surprising connection between these conjectures establishes a bridge between the quantum and the cosmic. By imposing specific constraints on the black hole's parameters, we demonstrate that the WGC and WCCC can be compatible in certain regions. We examine the properties of the KNKL black hole for q/m>(Q/M)ext, where (Q/M)ext is the charge-to-mass ratio of a large extremal black hole. We present figures to test the validity of both conjectures simultaneously. Without the spin parameter a, the cloud of string parameter b, quintessence parameter γ, and equation of state parameter ω, the black hole either has two event horizons if Q2/M2≤1 or none event horizon if Q2/M2>1 which leads to a naked singularity that contradicts the WCCC. However, when a, b, γ, and ω are present, the black hole has event horizons in some regions in the Q2/M2>1 that ensure the singularity is covered and both the WGC and WCCC are fulfilled. Actually, we face this issue in the extremality state of the black hole viz these conjectures remain viable, with the black hole maintaining an event horizon. We conclude that certain regions of a, b, γ, and ω parameters can make the WGC and WCCC compatible, indicating their agreement when these parameters are present.